Response to Salinity in Legume Species: An Insight on the Effects of Salt Stress during Seed Germination and Seedling Growth. Issue 4 (12th March 2021) - Tlahig, Samir; Bellani, Lorenza; Karmous, Inès; Barbieri, Francesco; Loumerem, Mohamed; Muccifora, Simonetta
Abstract: The process of soil salinization and the preponderance of saline water sources all over the world represent one of the most harmful abiotic stress to plant growth. This pointed to the importance of obtaining plants which are tolerant or resistant to salt, considering that projection of climate change for the coming years indicate an increase in temperature and rain scarcity. In the current study, the effect of NaCl was investigated on germinating seeds of Lathyrus sativus L., Vicia sativa L., Vigna radiata L. R.Wilczek and Vigna unguiculata L. Walp., by combining physiological, biochemical, biostatistical and ultrastructural analyses. Our results revealed that germination was not influenced by high NaCl concentrations, while seedling growth was affected even at low NaCl concentrations, probably due to an alteration in water uptake and in organic matter biosynthesis. Nevertheless, the synthesis of antioxidant enzymes, phenolic acids and flavonoids was registered in all species, which tended to cope with the increasing salt stress, allowing a response mechanism such as cytoplasm detoxification and cellular turgor maintenance. Besides, the ultrastructural analysis evidenced plasmolyzed cells close to cells with a normal ultrastructure with no appreciable differences among the species. This research deeply investigates the mechanism of salt‐stress response focusing on species never tested before for their possible tolerance to salinity. Abstract :